How Does Literature Affect Empathy in Students?. Issue 2 (3rd April 2017) - Junker, Christine R.; Jacquemin, Stephen J.
ABSTRACT: Scholars have suggested that reading literature can foster empathy. However, learning empathy through literature in the classroom is understudied. The primary objective of this study was to assess whether affective and cognitive empathy, as demonstrated in student writing, relates to textual attributes, the style of writing prompt, student writing ability, and whether it changes over time. Students in a college literature classroom were asked to assess texts according to a series of attributes related to engagement and textual difficulty, followed by a series of analytical and creative writing prompts. These responses were scored on a comparative scale according to metrics of empathy and compared with textual attributes, strength of writing, and time using a general linear model. Textual difficulty was identified as the greatest predictor of empathy (inverse relationship) followed by assignment grade (positive relationship). These results indicate that textual attributes, strength of writing ability, and style of writing response play a central role in explaining empathetic responses in students. The furthest-reaching implications of this study may, however, rest in the findings that empathy didn't change over the short time period and that textual accessibility may trump all other aspects in facilitating empathetic responses.